Prostate Cancer Risk in Relation to CYP3A4 and CYP3A5 Genotypes in the Bangladeshi Population (Dhaka University Journal of Pharmaceutical Sciences, 2016)
Genetic polymorphism on CYP3A4 and CYP3A5 gene and their associational susceptibility to prostate cancer was studied on Bangladeshi population, considering the importance of CYP3A4 and CYP3A5 gene in detoxification of xenobiotics from physiological territory. In this case control regulated study, we focused on two allelic variants CYP3A4 rs2740574 (CYP3A4*1B) and CYP3A5 rs776746 (CYP3A5*3) applying Polymerase Chain Reaction (PCR)-Restriction Fragment Length Polymorphism (RFLP). Associational risk on prostate cancer was estimated as odds ratio (OR) and 95% confidence interval (CI) using unconditional logistic regression models. An elevated prostate cancer risk was found with heterozygous, mutant and heterozygous plus mutant variants of CYP3A4*1B which is not statistically significant (p>0.05), whereas a significant association was found with heterozygous, mutant and heterozygous plus mutant variants of CYP3A5*3 (OR =4.36, 95%CI = 1.53 to 12.38, P =0.003; OR =3.85, 95%CI = 1.19 to 12.43, P = 0.017 and OR =4.13, 95%CI = 1.84 to 9.28, p =0.0006 respectively). The findings signposted a significant association of CYP3A5*3 gene and nullify the association of CYP3A4*1B genes polymorphism with prostate cancer risk in Bangladeshi subject.Dhaka Univ. J. Pharm. Sci. 14(2): 179-185, 2015 (December)